Geochemistry and mineral chemistry of gabbroic rocks from Horjand of Kerman province, Southeast of Iran: Implications for rifting along the northeastern margin of Gondwana. (January 2020) - Ghasempour, Mohammad Reza; Davoudian, Ali Reza; Shabanian, Nahid; Moeinzadeh, Hesamaddin; Nakashima, Kazuo
Abstract: The Horjand area is part of the Kashmar-Kerman tectonic zone in the Central Iranian block, where the oldest continental crust of Iran can be found. Mafic igneous rocks associated with sedimentary units (gypsum, shale, limestone, dolomite and sandstone) belong to the magmatism of the Late Neoproterozoic–Early Cambrian Desu Series. Based on petrographic studies, the mafic igneous rocks comprise medium to coarse gabbro, micro-gabbro and hornblende-gabbro. The rocks mainly consist of plagioclase, olivine, clinopyroxene, biotite, amphibole and Fe-Ti oxides. The gabbroic rocks have a variable compositional range, with SiO2 (44.6–52.9 wt. %), MgO (2.94–13.83 %), CaO (5.56–15.23 wt. %) and TiO2 (1.19–2.68 wt. %) contents. Petrographic evidence and geochemical data suggest that fractional crystallization has played an important role in the evolution of the ascending magma of the gabbroic rocks. The chemical composition of the minerals is similar to those of gabbroic rocks that were formed in a non-orogenic environment. The crystallization of clinopyroxene of gabbros mainly occurred under temperatures ranging from 1045 to 1216 °C. The geochemical characteristics and mineral compositions of the gabbros show that the samples predominantly have alkaline to minor tholeiitic affinities. During magma ascent, crustal contamination was minor or absent. Rare earth element modeling demonstrates that the magma of the Horjand gabbros was produced from 10 to 15 percent partial melting of a spinel-garnet lherzolite mantle source. Chondrite-normalized rare earth element (REE) patterns are LREE-enriched with (La/Yb)N of 4.50-12.82. Both normalized REE and trace-element spidergrams are similar to patterns of HIMU-OIB (high mu (μ = U/Pb)-ocean island basalt) or intraplate alkaline magmatic rocks. The gabbros geochemically display an intra-plate tectonomagmatic setting without subduction geochemical characteristics. Based on the available data and mineral chemical composition the development of the Horjand gabbroic rocks could be related to an extensional phase, with upwelling melting of the asthenospheric mantle in the continental rift resulting in alkaline magmatism of Late Neoproterozoic–Early Cambrian age, in the Central Iranian micro-continent.